The Feasibility of The Implementation of Forest Management Units' (FMUs') Policy: A Case Study in FMU Yogyakarta and FMU Region IX Panyabungan - Secunda Selamet Santoso; Dodik Ridho Nurrochmat; Bramasto Nugroho; Iman Santoso (Institut Pertanian Bogor (IPB University), 2019)
Operationalization of forest management units (FMUs) in Indonesia still requires assistance from the government. This research aimed to build a theoretical framework to enable FMU implementation on the ground. In addition, the criteria and indicators of FMU development were developed. The research implemented a quantitative approach by using Likert scale of rationality criteria and indicators. Two locations were selected for the analysis to comparing: maturity organization level, and forest farmer groups acceptance. Calculation rationality of FMU development was carried out using ten criteria and five indicators which were elaborated from the rationality of public policy which consists technical, legal, economic, social and substantive rationality. The rationality category was made by dividing three categories, namely rational, quite rational and irrational. The meaning of rational is that FMUs can carry out forest management, maintain forest area and carry out the long term forest management plan and the short term forest management plan programs that have been formulated as FMU's forest management plans. The result showed that FMU Yogyakarta is categorized as rational while the FMU in Region IX Panyabungan is categorized as quite rational. Low organizational capacity of FMU led to lower rationality of forest management. Improvement of forest management rationality can be carried out by building partnerships and collaboration with local people by providing legal access to manage forest areas. Optimal forest utilization will increase benefits and revenue forest management unit.